2007
DOI: 10.1152/jn.00752.2006
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Eye–Head Coordination After Injection of Muscimol Into the Interstitial Nucleus of Cajal (INC)

Abstract: . The interstitial nucleus of Cajal (INC) is thought to be the "neural integrator" for torsional/vertical eye position and head posture. Here, we investigated the coordination of eye and head movements after reversible INC inactivation. Three-dimensional (3-D) eye-head movements were recorded in three head-unrestrained monkeys using search coils. INC sites were identified by unit recording/electrical stimulation and then reversibly inactivated by 0.3 l of 0.05% muscimol injection into 26 INC sites. After musci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 94 publications
7
60
0
Order By: Relevance
“…This repetitive cycle of head movements is similar to the abnormal head movements provoked in monkeys by experimental perturbation of the proposed neural integrator for head control (Klier et al, 2002Farshadmanesh et al, 2007Farshadmanesh et al, , 2008. The repetitive head movements observed in normal subjects also resembled movements seen in patients with CD, prompting further exploration of the hypothesis that dysfunction of a neural integrator for head control underlies this disorder (Klier et al, 2002Farshadmanesh et al, 2007Farshadmanesh et al, , 2008. .…”
Section: Voluntary Head Movements In Healthy Subjectssupporting
confidence: 55%
See 2 more Smart Citations
“…This repetitive cycle of head movements is similar to the abnormal head movements provoked in monkeys by experimental perturbation of the proposed neural integrator for head control (Klier et al, 2002Farshadmanesh et al, 2007Farshadmanesh et al, , 2008. The repetitive head movements observed in normal subjects also resembled movements seen in patients with CD, prompting further exploration of the hypothesis that dysfunction of a neural integrator for head control underlies this disorder (Klier et al, 2002Farshadmanesh et al, 2007Farshadmanesh et al, , 2008. .…”
Section: Voluntary Head Movements In Healthy Subjectssupporting
confidence: 55%
“…The proposal that jerky OHM in CD are a form of head nystagmus is consistent with recent concepts of the pathogenesis of CD. Studies in animals have suggested that a circuit involving the interstitial nucleus of Cajal (INC) and the nucleus of Darkschewitsch serves as a neural integrator for holding the head steady (Hassler and Hess, 1954;Malouin and Bédard, 1982;Klier et al, 2002;Farshadmanesh et al, 2007;Klier et al, 2007). Experimental perturbations of these regions cause abnormal head postures along with OHM similar to those seen in CD.…”
Section: Relevance For Understanding Abnormal Head Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29] Unilateral iC lesion leads to ipsilesional TN and unilateral stimulation of the iC evokes ipsilateral eye torsion and head tilt in nonhuman. 30,31 In humans, iC lesion sparing riMLF may induce ipsilesional TN 28 and contraversive 32,33 or ipsiversive 28 ocular tilt reaction. Here, the dysfunction of vertical saccades is consistent with an inhibition of the riMLF but modulation of OTR can also suggest a stimulation of the iC.…”
Section: Videomentioning
confidence: 99%
“…The INC is an element of the indirect VOR pathway between the vestibular nuclei and ocular motor nuclei (31,32), comprising the vertical eye velocity-to-position integrator. Unilateral chemical inactivation of the simian INC has little or no effect on the vertical VOR (27,33), but the torsional gain is reduced (33). Bilateral INC lesions cause low VOR gain and a phase lead (27).…”
Section: Discussionmentioning
confidence: 99%